Ultrafast topological control - Song, Hyun Gyu; Gong, Su-Hyun (Nature Publishing Group, 2025)
Exciton–polariton superlattices allow sub-picosecond switching of topological phases, paving the way for ultrafast and reconfigurable topological photonic devices.